(3.4-2x)(3.4-2x)=0

Simple and best practice solution for (3.4-2x)(3.4-2x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3.4-2x)(3.4-2x)=0 equation:


Simplifying
(3.4 + -2x)(3.4 + -2x) = 0

Multiply (3.4 + -2x) * (3.4 + -2x)
(3.4(3.4 + -2x) + -2x * (3.4 + -2x)) = 0
((3.4 * 3.4 + -2x * 3.4) + -2x * (3.4 + -2x)) = 0
((11.56 + -6.8x) + -2x * (3.4 + -2x)) = 0
(11.56 + -6.8x + (3.4 * -2x + -2x * -2x)) = 0
(11.56 + -6.8x + (-6.8x + 4x2)) = 0

Combine like terms: -6.8x + -6.8x = -13.6x
(11.56 + -13.6x + 4x2) = 0

Solving
11.56 + -13.6x + 4x2 = 0

Solving for variable 'x'.

Begin completing the square.  Divide all terms by
4 the coefficient of the squared term: 

Divide each side by '4'.
2.89 + -3.4x + x2 = 0

Move the constant term to the right:

Add '-2.89' to each side of the equation.
2.89 + -3.4x + -2.89 + x2 = 0 + -2.89

Reorder the terms:
2.89 + -2.89 + -3.4x + x2 = 0 + -2.89

Combine like terms: 2.89 + -2.89 = 0.00
0.00 + -3.4x + x2 = 0 + -2.89
-3.4x + x2 = 0 + -2.89

Combine like terms: 0 + -2.89 = -2.89
-3.4x + x2 = -2.89

The x term is -3.4x.  Take half its coefficient (-1.7).
Square it (2.89) and add it to both sides.

Add '2.89' to each side of the equation.
-3.4x + 2.89 + x2 = -2.89 + 2.89

Reorder the terms:
2.89 + -3.4x + x2 = -2.89 + 2.89

Combine like terms: -2.89 + 2.89 = 0.00
2.89 + -3.4x + x2 = 0.00

Factor a perfect square on the left side:
(x + -1.7)(x + -1.7) = 0.00

Calculate the square root of the right side: 0.00

Break this problem into two subproblems by setting 
(x + -1.7) equal to 0.00 and 0.00.

Subproblem 1

x + -1.7 = 0.00 Simplifying x + -1.7 = 0.00 Reorder the terms: -1.7 + x = 0.00 Solving -1.7 + x = 0.00 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.7' to each side of the equation. -1.7 + 1.7 + x = 0.00 + 1.7 Combine like terms: -1.7 + 1.7 = 0.0 0.0 + x = 0.00 + 1.7 x = 0.00 + 1.7 Combine like terms: 0.00 + 1.7 = 1.7 x = 1.7 Simplifying x = 1.7

Subproblem 2

x + -1.7 = 0.00 Simplifying x + -1.7 = 0.00 Reorder the terms: -1.7 + x = 0.00 Solving -1.7 + x = 0.00 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.7' to each side of the equation. -1.7 + 1.7 + x = 0.00 + 1.7 Combine like terms: -1.7 + 1.7 = 0.0 0.0 + x = 0.00 + 1.7 x = 0.00 + 1.7 Combine like terms: 0.00 + 1.7 = 1.7 x = 1.7 Simplifying x = 1.7

Solution

The solution to the problem is based on the solutions from the subproblems. x = {1.7, 1.7}

See similar equations:

| 2.3-3= | | 876h+45-78=-0.9999 | | 41-8(-9)=6(-9)-23 | | 12x-28=-63+7 | | 384b^2-150c^2=0 | | 8y^3-24y^2-1664y=0 | | 54x+54*9=35x+45*9 | | t^2-5tx-50x^2=0 | | 10x+19x=15.40 | | 2x-18=42-4x | | 7+3ln(x)=6 | | (4,-1)=-3 | | 10x+19y=15.40 | | X^10x+1=9x+3 | | x/20.18=-7.35 | | 4z+21=5z | | 2x(5-7)+4=7x-2 | | -20.18/-7.35= | | 3x+43=9x+15 | | -7.35/-20.18= | | -7.9*24.36= | | 24.36*-7.9= | | q^2+4q+20=0 | | (4x+5)(3x+2)= | | -7.95/-6= | | -7.95*-6= | | (5-2x)+(-4x+9)=180 | | -7.95*-6=-13.25 | | -6*-7.95=-13.25 | | 5k-2y+4z-9k-3y-6z= | | 3m=m | | 5.6=80x-1.6 |

Equations solver categories